ChemInform Abstract: A Facile Route to Aqueous Ag:ZnCdS and Ag:ZnCdSeS Quantum Dots: Pure Emission Color Tunable over Entire Visible Spectrum. Issue 22 (15th May 2015) - Zeng, Ruosheng; Sun, Zhiguo; Cao, Sheng; Shen, Rongan; Liu, Zuoji; Long, Jintao; Zheng, Jinju; Shen, Yayun; Lin, Xiangnan
Abstract: Aqueous Ag:ZnCdS quantum dots (QDs) are prepared based on a co‐nucleation doping strategy using aqueous solutions of Cd(OAc)2, Zn(OAc)2 (in presence of mercaptopropionic acid; Cd:Zn molar ratio of 1:1), and AgNO3 at pH 7 to which a reactive S (and Se) powder precursor (hydrothermal S (Se) solution in presence of NaBH4 ) is given (autoclave, 180 °C, 2 h).